Α structural metaphor of techniques from music to architecture: contrapuntal tools in the design studio - KONSTANTINA DEMIRI (Joelho)
Architecture has historically more common elements with music than with the other arts. Their kinship lies not only on their mathematical base but also on their similar structural formation, compositional tools and terminology. Counterpoint in music is the technique of combining voices for a polyphonic form to be composed. In general, counterpoint is the art of manipulating a system of interrelations through which the whole is composed by its parts.